Survey Industri Kecil Menengah Logam di Desa Bengle Sebagai Upaya Pengembangan Ekonomi Lokal - Ananda Firza Ramadhan; Nisrina Nabila A`bidah; Muhamad Salsabil Fadilah; Heny Indriani; Budi Santoso; Muhamad Ainurohman; Mohammad Samsul Bakhri (MENGABDI : Jurnal Hasil Kegiatan Bersama Masyarakat, 2026)
Tegal Regency is a region in Central Java Province. Geographically, Tegal Regency is situated on a highly advantaged path. This regency, with its capital in Slawi, boasts a diverse range of economic centers spread across several regions. Dominated by small and medium-sized industries, the community can be empowered and participate in improving their well-being through job creation. Small and Medium Industry centers are highly diverse. One area we highlight in this article is the potential of metal and machinery SMEs, which are crucial commodities in the local economy. The metal industry is located around Talang District. The metal and machinery sector holds significant promise due to the potential for increased manufacturing demand, which can boost the local economy. In this study, we used field research and interviews to understand how the SME economy operates. By highlighting this, we hope that the government will focus on SMEs, particularly in the metal and machinery sector, by providing incentives for training and improving product quality and human resources. Based on the above description, local economic growth is highly possible with the support of adequate facilities and infrastructure.